2000
DOI: 10.1080/028418500127345596
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic falciform artery: Angiographic findings in 25 patients

Abstract: HFA is an extrahepatic pathway which runs to the abdominal wall. Before chemoembolization of the middle or left hepatic artery for hepatic malignancy, the HFA should be recognized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
14
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 6 publications
2
14
0
Order By: Relevance
“…Since late-2009, our institution has routinely performed SPECT/CT after liver-lung shunt scintigraphy. Our incidence of falciform ligament radiotracer activity detected on SPECT/ CT is 10% (5 out of 51 patients), in keeping with reported angiographic incidence [8][9][10][11][12][13]. However, this is likely an under-representation as some of our patients do not undergo whole-liver injection of Tc-99m-MAA.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Since late-2009, our institution has routinely performed SPECT/CT after liver-lung shunt scintigraphy. Our incidence of falciform ligament radiotracer activity detected on SPECT/ CT is 10% (5 out of 51 patients), in keeping with reported angiographic incidence [8][9][10][11][12][13]. However, this is likely an under-representation as some of our patients do not undergo whole-liver injection of Tc-99m-MAA.…”
Section: Discussionsupporting
confidence: 85%
“…The angiographic incidence of a patent hepatic falciform artery ranges from 2 to 24.5% [8][9][10][11][12][13]. Since late-2009, our institution has routinely performed SPECT/CT after liver-lung shunt scintigraphy.…”
Section: Discussionmentioning
confidence: 99%
“…It has an absorption peak at 608 nm in water and is known to stain collagen tissues well. 22,28 To our knowledge, the present study is the first time IC has been evaluated for vitreoretinal surgery, where it showed overall good safety about the retina. Such findings may indicate that IC and possibly other thiazine dyes may be useful in chromovitrectomy, but staining affinity issues should be evaluated.…”
Section: Discussionmentioning
confidence: 89%
“…The frequency identified by angiography is very low, only 2% from literatures [15,16] , until Song reported as 51.6% in a prospective study of angiography. Five cases of hepatic falciform artery were found in our study, all during the angiography of left hepatic artery.…”
Section: Discussionmentioning
confidence: 91%